RENCANA INDUK SISTEM PENYEDIAAN AIR MINUM KOTA SALATIGA - Saddam Pradika (Jurnal Teknik Lingkungan, 2013)
Salatiga is a city which located between Semarang District consist of 4 districts would need a water supply system to fullfill the water needs of the city. Water Supply System in Salatiga using gravity and pump systems with springs and deep well source. However, for a few years, people need new water sources to fulfill those needs. PDAM serve 56,14 % of Salatiga population. Salatiga has several potential sources of water which could be used as a source of raw water. Potential water source are needed to fullfill the water needs of each district in Salatiga so Salatiga require a Master Plan of Water Supply System.